2014
DOI: 10.1002/j.2161-1912.2014.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at Transgenerational Trauma Transmission: Second‐Generation Latino Immigrant Youth

Abstract: Transgenerational trauma, which was first documented in the 1960s to describe trauma symptoms experienced by descendants of holocaust survivors, has been linked to psychological and physiological transmission factors. Although traumatization still occurs among contemporary immigrant groups, particularly Latino immigrants, little attention has been paid to the experiences of these individuals. The authors present the relevant cultural considerations and conditions that support the need for proactive assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Forms of violence experienced by undocumented migrants include those associated with threats, verbal abuse, arbitrary detention based on ethnicity, as well as physical and sexual violence, all of which have been shown to affect migrants during their transit to the United States (Infante, Idrovo, Sánchez-Domínguez, Vinhas, & González-Vázquez, 2012). In addition, family separation and fear of deportation among undocumented immigrants can further compound the effects of trauma (Perreira & Ornelas, 2013; Phipps & Degges-White, 2014).…”
Section: Immigration-related Stressors and Protective Factors For Men...mentioning
confidence: 99%
“…Forms of violence experienced by undocumented migrants include those associated with threats, verbal abuse, arbitrary detention based on ethnicity, as well as physical and sexual violence, all of which have been shown to affect migrants during their transit to the United States (Infante, Idrovo, Sánchez-Domínguez, Vinhas, & González-Vázquez, 2012). In addition, family separation and fear of deportation among undocumented immigrants can further compound the effects of trauma (Perreira & Ornelas, 2013; Phipps & Degges-White, 2014).…”
Section: Immigration-related Stressors and Protective Factors For Men...mentioning
confidence: 99%
“…Mothers in a deeply traumatized state have more difficulty performing the basic tasks of attunement and mirroring necessary for healthy attachment with their child, who thus experiences relational trauma (Schore, ). Greater understanding of these mechanisms along with increased screening for Latino immigrant families, especially pregnant and new mothers and their infants, are essential to mitigate the effects of transgenerational trauma (Phipps & Degges‐White, ). Traumatic stress, violence exposure, and associations with reproductive justice, policy, and healthcare have been understudied.…”
Section: Relationship Of Maternal Well‐being and Reproductive Justicementioning
confidence: 99%
“…Latinx immigrants entering without legal documentation are forced to make longer transits, which makes them more susceptible to victimization, isolation, and discrimination (Infante et al, 2012;Perreira & Ornelas, 2011;Phipps & Degges-White, 2014;Shihadeh & Barranco, 2013). Unauthorized migration and the conditions it creates have the potential to make undocumented immigrants more prone to mental health issues, but there is little research done with this population, particularly studies focusing specifically on undocumented Latinx immigrant youth.…”
Section: Immigration Experiencesmentioning
confidence: 99%
“…Transgenerational trauma further expands the severity of traumatic migration experiences on mental health concerns of entire families and across multiple generations. Phipps and Degges-White (2014) found that Latinx families are extremely prone to transgenerational trauma due to their strong sense of familismo (e.g., strong loyalty to family, both immediate and extended). The oral history that is traditional of Latinx families is passed on and includes traumatic events, the content of which young Latinxs grow up internalizing as well as the negative emotions of the caretaker(s).…”
Section: Mental Health Risk Factors Related To Migrationmentioning
confidence: 99%